Socio-economic and Susceptibility Study of Dental Caries in Different Age Group People at Allahabad, India - Anupam Dikshit1*, Rohit Kumar Mishra1, Pravin Tiwari2 and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Abstract Dental caries is one of the most common infectious diseases in the human oral cavity. In developing countries like India, the rate of dental caries is rising because more than 80% of the world's children live in these countries; dental caries disease is considered to be a major public health problem. In this study total 180 saliva samples were collected from different age group, socioeconomic status, sex as well as different brushing schedule of peoples from Allahabad. On the basis of different age group peoples, the most susceptible (83.3%) was significantly higher age group 11-20 years followed by age group of >51 (73.3%), <10 (66.6%), 21-30 (63.3%), 41-50 (63.3%) and the lowest susceptible (53.3%) was noticed in age group of 31-40. Significantly higher dental caries susceptibility (86.66%) was noticed in lower class followed by Higher class (68.33%) where as the least with only 46.66% affected people was noticed in middle class. The significantly higher susceptibility to dental caries was seen 61.98% in male as compared to female 38.02%. The higher susceptibility to dental caries 78.57% in patient who brushed their teeth once in day, followed by whose brushed their teeth twice in day (63.46%), the minimum (36.66%) observed in patient whoâ€™s brushed their teeth thrice in day. Therefore, a need exists to identify individuals at risk for the disease, and to target preventive measures and active treatment for these individuals. Â  <div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> 1Biological Product Laboratory, Dept. of Botany, University of Allahabad, Allahabad-211002; 2Dental Surgeon, Saumya Dental Clinic, Taigore Town, Allahabad, India * Corresponding Author, Email: anupambplau@rediffmail.com Please Cite This Article As: Rohit Kumar Mishra, Pravin Tiwari and Anupam Dikshit. 2010. Socio-economic and Susceptibility Study of Dental Caries in Different Age Group People at Allahabad, India. J. Exp. Sci. 1(4):9-13.